PENGARUH DIKLAT DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI BADAN KEPEGAWAIAN, PENDIDIKAN DAN PELATIHAN KABUPATEN BOJONEGORO MELALUI MOTIVASI KERJA - Suliswanto, Suliswanto; Utari, Woro; Indrawati, Mei (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
This study aims to analyze the influence of training (Diklat) and organizational culture on work motivation and its impact on employee performance at the Human Resources Development and Training Agency of Bojonegoro Regency. Using a quantitative approach with explanatory research design, all 43 employees were selected as the sample through total sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method via SmartPLS 3.0. The results show that employees’ perceptions of all variables are generally in the “High” category. Organizational culture has a significant positive effect on work motivation, while training does not. Both training and work motivation have a significant positive effect on employee performance, whereas organizational culture does not have a direct effect. Indirectly, organizational culture significantly affects performance through motivation, while training does not.